Evaluation of Burkholderia mallei ΔtonB Δhcp1 (CLH001) as a live attenuated vaccine in murine models of glanders and melioidosis. - Nittaya Khakhum; Preeti Bharaj; Julia N Myers; Daniel Tapia; David H Walker; Janice J Endsley; Alfredo G Torres (Public Library of Science (PLoS), 2019)
Background Glanders caused by Burkholderia mallei is a re-emerging zoonotic disease affecting solipeds and humans. Furthermore, B. mallei is genetically related to B. pseudomallei, which is the causative agent of melioidosis. Both facultative intracellular bacteria are classified as tier 1 select biothreat agents. Our previous study with a B. mallei ΔtonB Δhcp1 (CLH001) live-attenuated vaccine demonstrated that it is attenuated, safe and protective against B. mallei wild-type strains in the susceptible BALB/c mouse model. Methodology/principal finding In our current work, we evaluated the protective efficacy of CLH001 against glanders and melioidosis in the more disease-resistant C57BL/6 mouse strain. The humoral as well as cellular immune responses were also examined. We found that CLH001-immunized mice showed 100% survival against intranasal and aerosol challenge with B. mallei ATCC 23344. Moreover, this vaccine also afforded significant cross-protection against B. pseudomallei K96243, with low level bacterial burden detected in organs. Immunization with a prime and boost regimen of CLH001 induced significantly greater levels of total and subclasses of IgG, and generated antigen-specific splenocyte production of IFN-γ and IL-17A. Interestingly, protection induced by CLH001 is primarily dependent on humoral immunity, while CD4+ and CD8+ T cells played a less critical protective role. Conclusions/significance Our data indicate that CLH001 serves as an effective live attenuated vaccine to prevent glanders and melioidosis. The quantity and quality of antibody responses as well as improving cell-mediated immune responses following vaccination need to be further investigated prior to advancement to preclinical studies.